Schottkyjeva bariera - Korošak, Dean (Vakuumist, 1998)
In the second part of the paper the transport mechanisms of the metal-semiconductor contact are discussed. An overview of the basic transport mechanism contributing to the current density through the ideal Schottky structure is given. An existance of possible additional charge transport mechanism due to the presence of the disordered interfacial control layer in the ICB deposited Schottky heterostrutures is further discussed. The influence of such a transport mechanism on the current-voltage characteristic is described.
Keywords: površine; kovine; polprevodniki; tanke plasti; naboj